Thermoplastics Polymers Friction Stir Welding: Review - Kamel Hussain, Randa; Abdul Majeed, Aseel (International Journal of Engineering and Technology, 2018)
Friction stir welding (FSW) is a relatively new technique has great potential it is an eco-friendly, low cost, used a wide range of materials and an excellent success to materials that un-fused. FSW technique recently developed for joining of thermoplastic polymeric materials and their composites. This review pointed to polymers welded by FSW method, focusing on previous articles that study the weld generation mechanisms. Displaying the explanations to reach a well understanding of polymer welding is presented in this review. The relationships and the effects of friction stir welding parameters on yield microstructure, phases, and mechanical properties were also re-discussed.